2017
DOI: 10.1016/j.meegid.2017.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Whole-genome characterization of Uruguayan strains of avian infectious bronchitis virus reveals extensive recombination between the two major South American lineages

Abstract: Infectious bronchitis virus (Gammacoronavirus, Coronaviridae) is a genetically variable RNA virus that causes one of the most persistent respiratory diseases in poultry. The virus is classified in genotypes and lineages with different epidemiological relevance. Two lineages of the GI genotype (11 and 16) have been widely circulating for decades in South America. GI-11 is an exclusive South American lineage while the GI-16 lineage is distributed in Asia, Europe and South America. Here, we obtained the whole gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 48 publications
0
18
1
1
Order By: Relevance
“…For easiness of representation, strain reported in the present study and closely related strains, are marked in red. (b) Expanded phylogenetic tree based on Maximum Likelihood method with Kimura-2 model constructed using S1 complete sequences closely related to gammaCoV/AvCov/Ck/Italy/IP14425/96 [Colour figure can be viewed at wileyonlinelibrary.com] accessory genes 4b, 4c, and 6b already reported for TCoV and other IBVs (Abolnik, 2015;Hewson, Ignjatovic, Browning, Devlin, & Noormohammadi, 2011 (Marandino et al, 2017) did not support the presence of ORF 6b in contrast to the results presented here. On the contrary, a recent study confirmed the expression of the 4b protein after M41 IBV infection in vitro (Bentley, Keep, Armesto, & Britton, 2013).…”
Section: Discussioncontrasting
confidence: 72%
“…For easiness of representation, strain reported in the present study and closely related strains, are marked in red. (b) Expanded phylogenetic tree based on Maximum Likelihood method with Kimura-2 model constructed using S1 complete sequences closely related to gammaCoV/AvCov/Ck/Italy/IP14425/96 [Colour figure can be viewed at wileyonlinelibrary.com] accessory genes 4b, 4c, and 6b already reported for TCoV and other IBVs (Abolnik, 2015;Hewson, Ignjatovic, Browning, Devlin, & Noormohammadi, 2011 (Marandino et al, 2017) did not support the presence of ORF 6b in contrast to the results presented here. On the contrary, a recent study confirmed the expression of the 4b protein after M41 IBV infection in vitro (Bentley, Keep, Armesto, & Britton, 2013).…”
Section: Discussioncontrasting
confidence: 72%
“…Betacoronaviruses are found mainly in mammals, such as humans, dogs, cats, pigs, bats, mice, rats, horses, and cattle 114,[118][119][120][121][122][123] , while Gama and Deltacoronaviruses infect mainly birds, with exceptions such as the white whale Gamacoronavirus (Delphinapterus leucas) 124 and the porcine Deltacoronavirus 125 .…”
Section: Coronavirus (Cov)mentioning
confidence: 99%
“…However, from the 1990s, its detection and reporting became sporadic or absent. At the same time, in 1996, a new IBV strain (later renamed Q1) was identified in animals affected by proventriculitis [13] in China and thereafter in other Asian [14,15], Middle Eastern [16,17], South American [18,19] and European countries [7,2022]. Remarkably, not recognizing the relationship between these strains, a new spread from Asia was supposed, similarly what was proven for the GI-19 lineage (QX genotype) [23].…”
Section: Introductionmentioning
confidence: 99%